On Q-algebras - Joseph Neggers; Sun Shin Ahn; Hee Sik Kim (International Journal of Mathematics and Mathematical Sciences)
We introduce a new notion, called a Q-algebra, which is a generalization of the idea of BCH/BCI/BCK-algebras and we generalize some theorems discussed in BCI-algebras. Moreover, we introduce the notion of quadratic Q-algebra, and show that every quadratic Q-algebra (X;∗,e), e∈X, has a product of the form x∗y=x−y+e, where x,y∈X when X is a field with |x|≥3.